Controlling the actuation properties of MXene paper electrodes upon cation intercalation. (October 2015) - Come, Jeremy; Black, Jennifer M.; Lukatskaya, Maria R.; Naguib, Michael; Beidaghi, Majid; Rondinone, Adam J.; Kalinin, Sergei V.; Wesolowski, David J.; Gogotsi, Yury; Balke, Nina
Abstract: Atomic force microscopy was used to monitor the macroscopic deformation in a delaminated Ti3 C2 paper electrode in situ, during charge/discharge in a variety of aqueous electrolytes to examine the effect of the cation intercalation on the electrochemical behavior and mechanical response. The results show a strong dependence of the electrode deformation on cation size and charge. The electrode undergoes a large contraction during Li +, Na + or Mg 2+ intercalation, differentiating the Ti3 C2 paper from conventional electrodes where redox intercalation of ions ( e.g . Li + ) into the bulk phase ( e.g . graphite, silicon) results in volumetric expansion. This feature may explain the excellent rate performance and cyclability reported for MXenes. We also demonstrated that the variation of the electromechanical contraction can be easily adjusted by electrolyte exchange, and shows interesting characteristics for the design of actuators based on 2D metal carbides. Graphical abstract: Highlights: Volume changes of 2D Ti3C2 MXene electrodes during cation intercalation are investigated. Large and reversible contraction is measured for Li+, Na+ and Mg2+ intercalation. The MXene actuation behavior can be controlled with a proper electrolyte selection. 2D titanium carbide electrodes are promising for tunable electromechanical actuators.